Peran Guru Kelas dalam Menanamkan Nilai Karakter Disiplin melalui Tata Tertib - Indah Kusumastutik; Rakanita Dyah Ayu Kinesti (YASIN, 2026)
Although MI NU Tarbiyatuth Thullab has implemented an adequate learning system and facilities, students’ discipline and cleanliness remain relatively low, as indicated by preliminary findings in Grade IV showing frequent violations of school regulations and low student participation in religious activities. This study aimed to describe the role of teachers in instilling disciplinary values in Grade IV students at MI NU Tarbiyatuth Thullab. The study employed a descriptive qualitative approach. Primary data were obtained through interviews with the principal, teachers, and Grade IV students, while secondary data were collected through documentation of madrasah activities. Data validity was examined through source triangulation, and data were analyzed through the stages of data reduction, data display, and conclusion drawing. The results showed that teachers played a strategic role in instilling disciplinary values through positive habituation, exemplary conduct, and collaboration with parents. These strategies proved effective in fostering responsibility, improving discipline, and cultivating clean and orderly behavior among students. Thus, the role of teachers is highly important in shaping students’ disciplinary character. The implications of this study emphasize the need to strengthen a culture of discipline continuously through collaboration among teachers, the madrasah, and parents so that disciplinary values can be applied consistently in daily life, both within and beyond the madrasah environment.